THE PRAGMATIC ANALYSIS OF DIRECTIVE SPEECH ACT TYPES IN THE MAIN CHARACTER’S UTTERANCES IN THE MOVIE “FREE GUY” - Agustinus Alwin Tango; Arie Ananda Putra; Rahmat Djihar; Ambalegin Ambalegin (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study applied a pragmatic study to obtain the types of directive speech acts in the movie "Free Guy” directed by Shawn Levy. The purpose of this study was to analyse the types of directive speech acts contained in the movie. Then, the speech was analysed and classified by applying the theory of Searle and Vanderveken (1985) to the data source. The data source for this research was the directive speech act uttered by the main characters in the movie "Free Guy". To get the desired research results, the research method used was descriptive qualitative method. Data collection technique was using observation technique and non-participation technique. Because too many the same data the researchers used data reduction method to reduce the same data. The data from this study was analysed using pragmatic method. The researchers found utterances of directive speech acts in the speech of the main characters. The researchers found 6 types of directive speech acts, including (2) Commanding, (4) Asking, (3) Request, (2) Ordering, (3) Suggest, and (1) Begging. The asking type of directive speech act was the most frequently found because the main character in this movie used to ask questions and the begging type was the type that was spoken the least.